Self-esteem and social media addiction level in adolescents: The mediating role of body image - Mehmet Colak; Ozlem Sireli Bingol; Ali Dayi (Indian Journal of Psychiatry)
Background: There are many studies examining the relationship between social media and self-esteem. Studies examining the relationships between the self-esteem, social media use, and body image of adolescents are limited in the literature. Aim: This study aimed to examine the relationship between self-esteem and social media addiction levels in adolescents and the mediating role of body image in the relationship between these two variables. Methods: The sample of the study consisted of 204 adolescents, 67 (32.8%) girls and 137 (67.2%) boys, with a mean age of 15.90 ± 1.20 years, who were high school students. The self-esteem levels of the participants were evaluated with the “Rosenberg Self-Esteem Scale”, their social media dependency levels were measured with the “Social Media Use Disorder Scale”, and their body images were measured using the “Multidimensional Body-Self Relations Questionnaire”. Results: No significant relationship was found between the self-esteem levels of the participants and their ages or the education levels of their parents. There was a negative moderate significant relationship between the self-esteem levels of the participants and their social media addiction levels, and a positive moderate significant correlation was found between their self-esteem levels and body images. It was found that the social media addiction levels of the participants negatively predicted their self-esteem and body image levels. It was determined that body image had a partial mediator effect on the relationship between the social media addiction and self-esteem levels of the participants. Conclusion: Our results revealed that there is a negative correlation between self-esteem and social media addiction levels in adolescents. Body image has a partial mediating role in the relationship between social media addiction and self-esteem levels.